DFT and experimental studies of oxygen adsorption on galena surface bearing Ag, Mn, Bi and Cu impurities. (February 2015) - Jianhua, Chen; Baolin, Ke; Lihong, Lan; Yuqiong, Li
Highlights: The influence of impurities on the electronic structure of galena surface was investigated by DFT. Adsorption of O2 on galena surface bearing impurities were simulated by DFT. The role of p -type and n -type in the adsorption of O2 on the galena surface was investigated. Interaction of impurity atom orbital with O atom orbital has been analyzed by DFT. Abstract: The adsorption of oxygen molecule (O2 ) on galena (1 0 0) surfaces containing Ag, Cu, Bi, and Mn impurities was investigated using density functional theory (DFT) method. The calculated results show that the impurities could change the semiconductor electronic structure of galena surface and influence the adsorption of oxygen molecule. The semiconductor type of Cu- and Ag-doped galena surfaces are p -type and that of Mn- and Bi-doped galena surface are n -type. Cu, Ag and Mn impurities greatly influence the Mulliken charge of adjacent S atoms, and the Bi impurity has small influence on galena surface. The adsorption of O2 on Cu-, Ag- and Bi-doped galena surface are stronger than that of the perfect galena, while the presence of Mn impurity weakens the adsorption of oxygen. For the Bi-doped galena, a strong interaction of Bi with O atom is observed. CV examinations results show that Cu- and Ag-doped galena have stronger oxidation peaks than perfect galena, and the CV curve of Bi-galena slightly enhance the oxidation of galena, while the oxidation peak is completely disappeared for Mn-galena.